Complete Genome Sequence of a Velogenic Newcastle Disease Virus Strain Isolated from a Clinically Healthy Exotic Parakeet (Melopsittacus undulatus) in Pakistan - Wajid, Abdul (Genome Announc, 2017)
The complete genome sequence of a virulent Newcastle disease virus (vNDV) strain isolated from an exotic parakeet (Melopsittacus undulatus) is described here. The virulent strain parakeet/Pak/R-Pindi/SFR-16/2016 was isolated from a bird reared as a pet in the province of Punjab in the northern region of Pakistan in 2016. Phylogenetic analysis classified the isolate as a member of NDV class II, subgenotype VIIi, in genotype VII.